FDI and ODA in SSA: Does it contribute to the SDGs? - Mathews, Candice (Graduate School of Business (GSB), 2024)
Sub-Saharan Africa (SSA) faces a persistent funding gap in financing its Sustainable Development Goals (SDGs). External finance flows are regarded as a key source of SDG financing. Therefore, can foreign flows in the form of Foreign Direct Investment (FDI) and Official Development Assistance (ODA) assist SSA in achieving the SDG goals? This study utilises panel data in a fixed effects model to investigate the influence of FDI and ODA on a sample of 32 SSA countries' SDG scores. The findings show a significant and positive influence of FDI on sustainable development, most notable in East and Southern African regions and with resource-rich countries. This impact is reflected in the overall general score and goals related to the economic and social pillars of the SDGs. However, there is no significant impact on the goals associated with the governance pillar. In fact, FDI has a negative relationship with the environmental aspect of sustainability. On the other hand, the social SDGs have been significantly and positively impacted by ODA. The study contributes to the current literature dedicated to financing sustainability, which can be helpful to emerging economies in understanding how to attract the right kind of external financing to close their funding gaps and meet their sustainable agenda.